Missus - Park, Ruth. (New York : St. Martin's Press, 1987)
Missus takes us behind the lives of Hughie and Mumma, out of the gritty realism of inner city slum life and into the past of the stations, the bush and the country towns. We meet them as they were in the early 1920s, drifter Hugh Darcy, the unwilling hero who sweeps the dreamily innocent Margaret Kilker off her feet. Ruth Park richly creates the turmoil of those early days of their courtship in the dusty outback, filled with beautifully drawn characters that will make you laugh as much as cry.
Keywords: HISTORICAL -- FICTION